Typhoon and climate history of northeastern Taiwan during mid to late Holocene: inferred through the Dahu Lake sediment core, Ilan Plain - Abdur Rahman; Liang-Chi Wang; Kaoru Kashima; Hong-Chun Li; Huei-Fen Chen; Tien-Nan Yang (PANGAEA, 2025)
A 35-meter-long sediment core (DH-7B) was retrieved from Dahu Lake using a stainless-steel pipe mounted on a floating platform. The core was subsampled at 5-cm intervals with 1-cm thickness for diatom, stable isotope, and trace element analyses. To establish the core chronology, 11 samples containing peat and plant remains were collected during subsampling, oven-dried at 40?°C, and dated by Accelerator Mass Spectrometry (AMS) at the AMS Laboratory, National Taiwan University. For diatom analysis, 0.5?g of dry sediment was treated with 32% H?O? and 10% HCl. The cleaned material was mounted on slides using Wako mounting medium, and 300 diatom valves were identified and counted under an optical microscope at 1000 exttimes magnification. For the analysis of carbon isotopic composition in organic carbon (δ^1^3C), powdered samples were decarbonated overnight with HCl. After complete removal of inorganic carbon, the residues were washed with ultrapure water (Milli-Q) by centrifugation three to four times, then dried at 60?°C overnight. The dried samples were encapsulated in tin and combusted at 1000?°C in a Flash 2000 Elemental Analyzer (Thermo Scientific). The resulting CO? was analyzed by isotope ratio mass spectrometry (IRMS; Delta V Advantage, Thermo Scientific) via a ConFlo interface using He as the carrier gas. The ^1^3C/^1^2C ratios were reported in δ notation relative to the Vienna Pee Dee Belemnite (VPDB) standard. The USGS 40 standard (L-glutamic acid, δ^1^3C = -26.39 ± 0.04 extperthousand; C content = 40.8%) was used to monitor instrument performance. Analytical precision was ±0.1 extperthousand for δ^1^3C and <10% for C content. Total nitrogen (N) content was measured simultaneously using the jump method in the same run. For trace element analysis, dry sediment samples (0.5?g) were collected at 2-cm intervals and leached with 10?mL of 0.5N HCl. The resulting supernatant was analyzed for Ca, Mg, Sr, Ba, K, Na, Li, Fe, Mn, Al, Zn, and Cu using inductively coupled plasma optical emission spectrometry (ICP-OES)., and Pb.